Comparative analysis of perceived security level in deciding the use of e-banking in Y and Z generations - Siti Alhamra Salqaura; Indawati Lestari; Teddi Pribadi (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2023)
This study aimed to compare perceptions of the security level in making decisions on the use of e-banking in the Y and Z generations. Sampling was carried out using a purposive sampling method. The respondents in this study were e-banking consumers in the Y and Z generations. Data were analyzed using the Mann-Whitney U Test through SPSS software version 20.00. The research results show no significant difference in the perceived security in usage decisions of E-Banking Y and Z generations.